2021
DOI: 10.1111/camh.12505
|View full text |Cite|
|
Sign up to set email alerts
|

Review: Economic evidence of preventive interventions for anxiety disorders in children and adolescents – a systematic review

Abstract: Background: Anxiety disorders are common in children and youth. Also, in prevention, be it universal, selective or indicated, economic evaluation supports decision-making in the allocation of scarce resources. This review identified and summarised the existing evidence of economic evaluations for the prevention of anxiety disorders in children and adolescents. Methods: A systematic search was conducted on the EBSCO, Scopus, Web of Science, ProQuest, Cochrane and PubMed databases. We included studies that focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
(224 reference statements)
0
1
0
Order By: Relevance
“…Youth mental health services in the UK have been cited as lacking in community-based services and preventative, early interventions (Vusio et al, 2021). A recent review has tentatively suggested parent training and early, preventative cognitive behavioural therapy (CBT) interventions could be cost-effective approaches to reduce anxiety related distress for young people (Anna-Kaisa et al, 2022). In addition, cross-service collaborations and early intervention models show promise (Tudor, 1996), as children and young people are often particularly vulnerable to environmental factors, such as parental addiction or unemployment (Coates, 2017).…”
mentioning
confidence: 99%
“…Youth mental health services in the UK have been cited as lacking in community-based services and preventative, early interventions (Vusio et al, 2021). A recent review has tentatively suggested parent training and early, preventative cognitive behavioural therapy (CBT) interventions could be cost-effective approaches to reduce anxiety related distress for young people (Anna-Kaisa et al, 2022). In addition, cross-service collaborations and early intervention models show promise (Tudor, 1996), as children and young people are often particularly vulnerable to environmental factors, such as parental addiction or unemployment (Coates, 2017).…”
mentioning
confidence: 99%